THE ROLE OF STRATEGIC MANAGEMENT IN ADMINISTRATIVE DEVELOPMENT IN IMPROVING JOB PERFORMANCE-AN APPLIED STUDY ON EMPLOYEES AT THE UNIVERSITY OF BAGHDAD (World Economics and Finance Bulletin, 2024)
This study aimed to study the role of the Administrative Development Department in improving the job performance of female administrative employees at King Baghdad University by answering the following questions: What is the role that the Development Department seeks to achieve in cooperation with all departments or departments within the university? What is the impact of development on employee performance? What is the role of senior management in each entity in implementing development processes in cooperation with the Administrative Development Department? What are the challenges facing the development process, and ways to overcome them? What activities does the Administrative Development Department provide in the field of improving job performance in cooperation with departments and divisions within the university
Keywords: University of Baghdad; strategic management; employees